Labour Law in Namibia - Parker, Collins (Book collections on Project MUSE., 2012)
Labour Law in Namibia is the first comprehensive and scholarly text to analyse labour law in the country, the Labour Act of 2007, and how it affects the common law principles of employment relations. Concise and extensively researched, it examines the Labour Act in detail in 16 chapters that include the employment relationship; duties of employers and employees; unfair dismissal and other disciplinary actions; the settlement of industrial disputes; and collective bargaining. Over 500 relevant cases are cited, including court rulings in other countries, and comparative references to the labour.